Only the brave [videorecording (DVD)] - Brolin, Josh; Teller, Miles; Bridges, Jeff, 1949-; Flynn, Sean, 1964- (Sony Pictures Home Entertainment, 2018)
Based on the true story of the Granite Mountain Hotshots, a group of elite firefighters risk everything to protect a town from a historic wildfire.